2021
DOI: 10.3390/biom11040550
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RNA in DNA Breaks, Repair and Chromosomal Rearrangements

Abstract: Incorrect reparation of DNA double-strand breaks (DSB) leading to chromosomal rearrangements is one of oncogenesis’s primary causes. Recently published data elucidate the key role of various types of RNA in DSB formation, recognition and repair. With growing interest in RNA biology, increasing RNAs are classified as crucial at the different stages of the main pathways of DSB repair in eukaryotic cells: nonhomologous end joining (NHEJ) and homology-directed repair (HDR). Gene mutations or variation in expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 176 publications
(192 reference statements)
0
9
0
Order By: Relevance
“…By now RNA molecules have been established as key players in most genome related processes 13,45,46 . However, only a few works have been devoted to the role of RNA in the stimulation of directed chromosome rearrangements in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By now RNA molecules have been established as key players in most genome related processes 13,45,46 . However, only a few works have been devoted to the role of RNA in the stimulation of directed chromosome rearrangements in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…These RNAs determine which parts of the genome are excised and which should be joined and in what order 12 . In human cells, a number of studies have previously reported that lncRNAs are involved in the regulation of reparation and nascent RNAs can control the fidelity of this process via complementary interactions with the joining DNA fragments 13,14 . This evidence, albeit sparse at the moment, indicates that lncRNAs are indeed involved in chromosomal rearrangements in humans.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that although there is some evidence for rRNA and tRNA involvement in DDR, these are not covered in this review. The activation of DNA repair by RNA transcripts synthesised in trans has been widely studied and reviewed [4,8,21,22]. These RNA transcripts are commonly ncRNA species, which can be further classified into long non-coding RNA (lncRNA) or small non-coding microRNA (miRNA) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can lead to DNA damage, including ionizing 2 of 18 and UV radiation, oncogene activation, exposure to chemical carcinogens and viral infections [1,2]. DSB formation is more frequently observed in the proximity of DNA:RNA hybrids known as R-loops [3,4]. R-loops can form in the process of transcription or during the interaction of DNA with regulatory RNAs resulting in DNA double strand separation, which renders DNA more vulnerable to genotoxic stress [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of evidence has demonstrated that several types of RNA species hold critical roles in various nuclear processes, such as DNA replication and repair, chromosome structure regulation, telomere elongation and chromatin organization [4,[7][8][9]. A large number of eukaryotic protein-coding genes have been found capable of generating exonic circular RNAs (circRNAs), which may exist at higher levels than their respective linear mRNAs [10], as the circRNAs have an increased life due to resistance to RNA degradation via exonucleases and can thus accumulate to levels that can even exceed the life of their cognate linear mRNAs [11].…”
Section: Introductionmentioning
confidence: 99%